2018
DOI: 10.2147/ott.s156723
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis for patients with newly diagnosed glioblastoma receiving bevacizumab combination therapy: a meta-analysis

Abstract: BackgroundA combination of temozolomide (TMZ) and radiotherapy and subsequent adjuvant chemotherapy is the gold standard of treatment for glioblastoma (GB). Bevacizumab (BEV), a humanized monoclonal antibody that blocks the effects of vascular endothelial growth factor A, has produced impressive response rates for recurrent GB and has been approved as second-line therapy. The efficacy and safety of BEV in newly diagnosed GB are not known.AimThis systematic meta-analysis was undertaken to evaluate the value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…The study of Li et al 27 showed that the PFS time at 24 months and 36 months in the BEV group was lower than that in the non-BEV group. The results of Liao et al 28 showed that a higher incidence of PFS could be obtained by adding BEV to newly diagnosed Glioblastoma (GB), and this combined treatment did not improve OS. The AVA glio 29 trial showed that patients treated with BEV had significant advantages in PFS (6.2 months vs 10.6 months) and maintenance of life quality, but showed no advantages in OS (16.8 months vs 16.7 months).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Li et al 27 showed that the PFS time at 24 months and 36 months in the BEV group was lower than that in the non-BEV group. The results of Liao et al 28 showed that a higher incidence of PFS could be obtained by adding BEV to newly diagnosed Glioblastoma (GB), and this combined treatment did not improve OS. The AVA glio 29 trial showed that patients treated with BEV had significant advantages in PFS (6.2 months vs 10.6 months) and maintenance of life quality, but showed no advantages in OS (16.8 months vs 16.7 months).…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is a highly malignant primary tumor of the central nervous system, accounting for approximately 12–15% of all brain tumors (Davis, ). The current standard therapy is Temozolomide (TMZ) associated to radiotherapy (Liao, Huang, & Wu, ). Furthermore, development of the genomic technology leads to the identification of markers able to manage the proper therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy has been used across various cancer types in an effort to reduce the likelihood of multidrug resistance from efflux pumps and P-glycoproteins in the cell membrane of cancer cells, for example [29,30,31,32,33]. The tumor microenvironment is characterized by acidic pH, hypoxia and increased interstitial pressure, all of which promote the heterogeneous cell populations which are resistant, quickly adapting and mutating [34,35].…”
Section: Introductionmentioning
confidence: 99%